1999
DOI: 10.1182/blood.v93.3.780
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Derived In Vitro From Acute Myelogenous Leukemia Cells Stimulate Autologous, Antileukemic T-Cell Responses

Abstract: We have previously reported that leukemic dendritic cells (DC) can be generated ex vivo from myelomonocytic precursors in chronic myelogenous leukemia. In this study we report the generation of DC from acute myelogenous leukemia (AML) cells and their potent ability to stimulate leukemia-specific cytolytic activity in autologous lymphocytes. DC were generated in vitro using granulocyte-macrophage colony-stimulating factor +interleukin-4 in combination with either tumor necrosis factor- or CD40 ligand (CD40L). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(40 citation statements)
references
References 12 publications
3
36
1
Order By: Relevance
“…In contrast to other AML blast-derived DCs [12][13][14], the current study indicates that DC-like leukemia already expresses some DC characteristics without the requirement of ex vivo culture in the presence of cytokines. According to the French-American-British (FAB) classification, DC-like leukemic cells may be similar to blasts of mature monocytic leukemia [M5b, defined as follows: Differentiated monocytic leukemic cells with a large cerebriform nucleus are found in a higher proportion in the PB than in the bone marrow (BM)] [17,18]; however, these cells are unique in phenotype and function.…”
Section: Introductioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In contrast to other AML blast-derived DCs [12][13][14], the current study indicates that DC-like leukemia already expresses some DC characteristics without the requirement of ex vivo culture in the presence of cytokines. According to the French-American-British (FAB) classification, DC-like leukemic cells may be similar to blasts of mature monocytic leukemia [M5b, defined as follows: Differentiated monocytic leukemic cells with a large cerebriform nucleus are found in a higher proportion in the PB than in the bone marrow (BM)] [17,18]; however, these cells are unique in phenotype and function.…”
Section: Introductioncontrasting
confidence: 53%
“…The PBMC of some patients with acute myelogenous leukemia (AML) or chronic myelogenous leukemia (CML) with addition of cytokines can sometimes be induced to differentiate into a newly elucidated, malignant counterpart of myeloid DCs, based on phenotypic and functional characteristics, such as the ability to stimulate antigen-specific cytotoxic T cells (CTLs) [11][12][13][14][15]. As a result, these leukemic cells have been envisioned as useful therapeutic reagents for treatment in patients.…”
Section: Introductionmentioning
confidence: 99%
“…A dendritic AML cell phenotype can be induced by in vitro culture of native AML cells in the presence of exogenous cytokines (65)(66)(67)(68). Previous detailed characterization of our in vitro model has demonstrated that these cells have a leukemic origin and their phenotype includes (56): (i) production of cytokines that support T-cell activation and drive Th1 polarization; (ii) generation of autologous, leukemia-specific and HLA-restricted CD8 + and CD4 + T-cell responses; (iii) migration from tissues to lymph nodes; (iv) amplification of antigen presentation by monocyte attraction; (v) attraction of naive ⁄ resting and activated T cells.…”
Section: Cyclin B1 In Amlmentioning
confidence: 99%
“…Several investigators have now shown that under the influence of GM-CSF and IL-4 in combination with tumour necrosis factor-a (TNF-a), and CD40L or FLT3-L, AML cells can differentiate into DC, irrespective of their FAB classification and clinical status. [79][80][81][82][83] Under these conditions, the AML-differentiated DC unlike their original blasts, express molecules typical of DC markers including CD1a, CD83, B7.1 and B7.2, CD40 and high-class I and class II. In these studies, the AML-differentiated DCs have been shown to be effective at stimulating both allogeneic and autologous T-cell proliferative responses.…”
Section: Dendritic Cells and Vaccination Strategiesmentioning
confidence: 99%